2019
DOI: 10.1088/1555-6611/ab3636
|View full text |Cite
|
Sign up to set email alerts
|

Cross-focusing of a quadruple Gaussian laser beam in plasma in the relativistic regime

Abstract: The present study explores the phenomenon of cross-focusing of two quadruple Gaussian laser beams, each comprising four identical Gaussian beams whose axes are in the z-direction but shifted from the z-axis by a distance x o along positive and negative x-and y -axes in an underdense plasma. The nonlinearity arising due to the relativistic mass effect is taken into consideration. Nonlinear partial differential coupled equations governing the dynamics of two beams are solved using the paraxial ray approximation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Utilizing moment theory, the self-focusing of quadruple Gaussian beams in relativistic plasma was analyzed, revealing that self-focusing increases with larger beam separation and higher plasma density. Additionally, investigations on cross-focusing of two quadruple Gaussian beams have demonstrated enhanced beam focusing through the cross-focusing mechanism [42].…”
Section: Introductionmentioning
confidence: 99%
“…Utilizing moment theory, the self-focusing of quadruple Gaussian beams in relativistic plasma was analyzed, revealing that self-focusing increases with larger beam separation and higher plasma density. Additionally, investigations on cross-focusing of two quadruple Gaussian beams have demonstrated enhanced beam focusing through the cross-focusing mechanism [42].…”
Section: Introductionmentioning
confidence: 99%
“…Due to the high penetration and non-ionization properties, THz radiation found to have multitudinous applications in the field of medical diagnostics [1][2][3], spectroscopy, remote sensing, material characterization [4][5][6], security-safety, non-destructive testing, explosive detection [7,8], communication [9] and many more. For the development of innovative, proper, efficient, powerful, and compact THz sources various schemes have been suggested by the researchers, for example, THz waves by using filamentation of laser beams [10], by cross-focusing of laser beams in carbon nanoparticles and carbon nanotubes [11,12], nonlinear interaction of laser beams in the CNTs and, semiconductors [13][14][15][16]. From these schemes, it is observed that CNTs because of nano dimensions, excellent thermal transport, and electrical conductivity provide better conversion efficiency to obtain strong THz emissions.…”
Section: Introductionmentioning
confidence: 99%